2013
DOI: 10.1002/bjs.9296
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of single-incision versus conventional multiport appendicectomy

Abstract: SILA is a safe procedure for the treatment of acute appendicitis, with comparable clinical outcome to CLA when undertaken by experienced laparoscopic surgeons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 27 publications
2
29
0
4
Order By: Relevance
“…Random sequence generation SILA has emerged as a potential less invasive approach, and has been demonstrated to be comparable to CLA among the adult population by numerous meta-analyses [9][10][11][12][13][14][15][16][17][18], but systematic reviews that are focused on pediatric populations are still lacking. A child half as tall as an adult only provides one-eighth of the working space in the abdomen to the surgeon [42].…”
Section: Referencesmentioning
confidence: 99%
“…Random sequence generation SILA has emerged as a potential less invasive approach, and has been demonstrated to be comparable to CLA among the adult population by numerous meta-analyses [9][10][11][12][13][14][15][16][17][18], but systematic reviews that are focused on pediatric populations are still lacking. A child half as tall as an adult only provides one-eighth of the working space in the abdomen to the surgeon [42].…”
Section: Referencesmentioning
confidence: 99%
“…Although there was a trend toward higher incidence of abscess formation using SILA technique (2.7% vs 1.3%), this did not reach significance [44]. A meta-analysis published in 2013 included many of the same studies, including those conducted in the pediatric population and found no statistical difference in the rates of IAA among SILA patients (1.8%) and conventional laparoscopy (1.3%) [45]. Table 5 highlights these and other meta-analyses comparing SILA with LA.…”
Section: Single-incision Laparoscopic Appendectomymentioning
confidence: 76%
“…The above has been source of controversy among surgeons, since many argue that the SIL transgresses the principles of laparoscopic surgery by not counting with triangulation, among other features 32 .…”
Section: Discussionmentioning
confidence: 99%